2014
DOI: 10.1155/2014/348659
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Repeatability of the Gait Analysis by the WalkinSense System

Abstract: WalkinSense is a new device designed to monitor walking. The aim of this study was to measure the accuracy and repeatability of the gait analysis performed by the WalkinSense system. Descriptions of values recorded by WalkinSense depicting typical gait in adults are also presented. A bench experiment using the Trublu calibration device was conducted to statically test the WalkinSense. Following this, a dynamic test was carried out overlapping the WalkinSense and the Pedar insoles in 40 healthy participants dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 33 publications
(61 reference statements)
2
32
0
Order By: Relevance
“…However, neither have ever been utilized in clinical practice because of complications in measurement and data processing. Conversely, wearable sensors including magnetic and inertial measurement units (IMU), permitting the objective and simple assessment of human movement, have become widely used tools in motion analysis [25][26][27][28][29][30]. TLA might be estimated from thigh and shank segment angles obtained by IMU.…”
Section: Introductionmentioning
confidence: 99%
“…However, neither have ever been utilized in clinical practice because of complications in measurement and data processing. Conversely, wearable sensors including magnetic and inertial measurement units (IMU), permitting the objective and simple assessment of human movement, have become widely used tools in motion analysis [25][26][27][28][29][30]. TLA might be estimated from thigh and shank segment angles obtained by IMU.…”
Section: Introductionmentioning
confidence: 99%
“…However, Alghadier [2] concluded that carrying a backpack significantly altered the dynamic foot-loading patterns (peak plantar pressure, peak plantar force and contact area) in school-age children (7-12 years), which goes against the current findings. The cause of disagreement may be the difference in the nature of the measured outcomes; the GRFs do not provide any information about where the forces are being applied on the foot [9], whereas the in-shoe plantar pressure systems allow quantification of the amount of vertical GRF being applied on each region of the plantar surface of the foot [11]. However, Castro et al [8] found greater normalized anterior-posterior and vertical GRFs and greater plantar pressure peaks in the rearfoot, forefoot and hallux when adult participants walked carrying a backpack at high gait cadences compared to walking at low gait cadences.…”
Section: Discussionmentioning
confidence: 99%
“…It contains a triaxial accelerometer, a gyroscope, and eight piezoresistive pressure sensors. Castro et al [131] used the system to track 40 healthy participants during walking in which it demonstrated a high accuracy for plantar pressure variables. While most systems use insoles with fixed sensor locations, the W-INSHOE system is equipped with nine resistive pressure sensors which can be positioned freely to any part of the foot or shoe, allowing users to adjust the sensor location easily.…”
Section: A Commercial Footwear Systemsmentioning
confidence: 99%